2017
DOI: 10.1021/acs.analchem.7b03133
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Sensitive Detection of Methylcytosine by Aerolysin Nanopore under Serum Condition

Abstract: Detection of DNA methylation in real human serum is of great importance to push the development of clinical research and early diagnosis of human diseases. Herein, taking advantage of stable pore structure of aerolysin in a harsh environment, we distinguish methylated cytosine from cytosine using aerolysin nanopore in human serum. Since wild-type (WT) aerolysin enables high sensitivity detection of DNA, the subtle difference between methylated cytosine and cytosine could be measured directly without any specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 34 publications
2
54
0
Order By: Relevance
“…Next, the voltage‐dependent studies were conducted which revealed that the duration of Teln decreased exponentially with the applied voltage ranging from +120 to +180 mV ( Figure a). These results were consistent with our previous researches and confirmed the translocation of Teln through the aerolysin nanopore. The free energy barrier is associated with the transport of oligonucleotides.…”
Section: Statistical Results Of the Duration And The I/i0 For Teln (Nsupporting
confidence: 94%
See 1 more Smart Citation
“…Next, the voltage‐dependent studies were conducted which revealed that the duration of Teln decreased exponentially with the applied voltage ranging from +120 to +180 mV ( Figure a). These results were consistent with our previous researches and confirmed the translocation of Teln through the aerolysin nanopore. The free energy barrier is associated with the transport of oligonucleotides.…”
Section: Statistical Results Of the Duration And The I/i0 For Teln (Nsupporting
confidence: 94%
“…Next, the voltage-dependent studies were conducted which revealed that the duration of Teln decreased exponentially with the applied voltage ranging from +120 to +180 mV (Figure 3a). These results were consistent with our previous researches [8,[26][27][28] Small 2018, 14, 1704520 Figure 2. Translocation of unfolded Teln (n = 1, 2, 3, 4, and 5) through an aerolysin nanopore in MgCl 2 solution.…”
Section: Doi: 101002/smll201704520supporting
confidence: 93%
“…The technologies presented above show the future potential for the identification of epigenetic modification or single nucleotide polymorphism on DNA using the nanopore-nucleic acid interaction [52,53,61,62]. In addition, the nanopore coupled with a complementary DNA would facilitate the early detection of pathogenic DNA, shown in the detection of the anthrax-related DNA of Bacillus anthracis [63].…”
Section: Chemical and Biomolecular Sensingmentioning
confidence: 99%
“…26 This study demonstrated the possibility that ARP systems could be utilized for highly sensitive and specific detection of single base variations, including the identification of gene mutations and base modifications. Later, Long’s group 27 reported that an ARP system could discriminate methylcytosine (mC) from C (5′-CAAA-3′ vs. 5′-mCAAA-3′) in serum. The translocation frequency of methylated cytosine correlated with its relative concentration (Fig.…”
Section: Direct Discrimination Of a T C And G Nucleobases As Well mentioning
confidence: 99%